Constitutions as Mediums of Collective Identities - Lukáš Lev Červinka (German Law Journal, 2024)
When we think about constitutions, we tend to see them predominantly through the normative lens of legality, forgetting about the social implications of constitutions and the lives thereof. And even when we do study them from a more socio–legal perspective, we usually associate them solely with the state. This understanding of constitutions is the legacy of not only a state–centric approach in legal science but also of an institutional approach, particularly in political science. It shapes our understanding of constitutions as legal regulations of an institutional framework of the state and the conduct of politics. Moreover, the liberal tradition compels us to see constitutions as tools to restrain the power of the state and ensure the rights and liberties of individuals; that is, as tools of the liberal rule of law.